Reading music from screens vs paper - Picking, Richard (Behaviour & information technology, 1997)
The reading of music text from a computer screen was compared to paper in a laboratory controlled study. Computer-based animated score tracking devices of three types were tested, as well as a static screen representation of the music text and its paper-based counterpart. A proof-reading exercise was given to subjects, which involved them listening to pieces of music and identifying intentional errors in the score. Their subjective views were also recorded. No significant difference between the five presentation styles were apparent in the proofreading study. However, subjects showed a significant preference for animation over paper and static representation. The most popular style of animation was where each note on the score was marked in time to the music. The medium of paper performed better overall than the static screen representation.